2018
DOI: 10.1002/ppul.24128
|View full text |Cite
|
Sign up to set email alerts
|

Club cell secretory protein (CC16) in gastric fluid at birth and subsequent lung disease in preterm infants

Abstract: A low CC16 concentration in gastric fluid at birth was associated with increased inflammation in the trachea within the first 24 h of life and with more need for respiratory support in the neonatal period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Club cell protein (CC16), a secretory protein found at extremely high levels in the lungs, is widely believed to be of great significance in anti-inflammatory and antioxidant stress [8, 9]. Studies performed to understand the roles of CC16 have revealed that recombinant CC16 (rCC16) not only shows therapeutic effects in disease models but also helps mitigate the respiratory function of premature infants and newborn lambs [1012].…”
Section: Introductionmentioning
confidence: 99%
“…Club cell protein (CC16), a secretory protein found at extremely high levels in the lungs, is widely believed to be of great significance in anti-inflammatory and antioxidant stress [8, 9]. Studies performed to understand the roles of CC16 have revealed that recombinant CC16 (rCC16) not only shows therapeutic effects in disease models but also helps mitigate the respiratory function of premature infants and newborn lambs [1012].…”
Section: Introductionmentioning
confidence: 99%
“…Another study documented that OVA-challenged CC16 −/− mice exhibited more severe airway dysfunction than wild mice [26]. Also, a low concentration of CC16 in gastric uid at birth was thought to be correlated with increased lung in ammation in the neonatal period [27].Thus, on the basis of detailed prior studies of the role of CC16 in airway diseases, we postulated that supplementary CC16 may restore airway in ammation in HDM-induced asthma. In the current study, by the establishment of an experimental model of murine asthma, our results demonstrated that exogenous administration of CC16 decreased in ammatory cells counts and Th2 cytokines levels including IL-4, IL-5, IL-13 as well as HDM-speci c IgE in the BALF of asthmatic mice.…”
Section: Discussionmentioning
confidence: 91%
“…Not only markers of injury, but maladaptive decrements of protective factors may portend BPD. Hagman and colleagues correlated gastric concentrations of club cell secretory protein 16 (CC16, previously termed CC10, CCSP, the gene product of SCTGB1A1 ) with evidence of lung inflammation at birth and the risk to require higher respiratory support . A protective role against inflammation has long been ascribed to this protein, so it might be expected that low lung production—inferred from gastric contents that are largely amniotic fluid and hence in contact with the fetal lung—may represent impaired lung development or reduced anti‐inflammatory capacity.…”
Section: The Canary In the Coal Shaft: The Hunt For Early Markersmentioning
confidence: 99%
“…Hagman and colleagues correlated gastric concentrations of club cell secretory protein 16 (CC16, previously termed CC10, CCSP, the gene product of SCTGB1A1) with evidence of lung inflammation at birth and the risk to require higher respiratory support. 19 A protective role against inflammation has long been ascribed to this protein, so it might be expected that low lung production-inferred from gastric contents that are largely amniotic fluid and hence in contact with the fetal lung-may represent impaired lung development or reduced anti-inflammatory capacity. The authors found that gastric fluid and tracheal aspirate concentrations of CC16 correlated poorly, possibly due in part to small sample sizes but possibly attributable to dilution of the tracheal samples.…”
Section: The Canary In the Coal Shaft: The Hunt For Early Markersmentioning
confidence: 99%